Method construction of swimming pool slab / Nurul Hayati Mohamad - Mohamad, Nurul Hayati (Universiti Teknologi MARA, Perak, 2015)
An in-situ concrete suspended floor is one constructed with reinforced concrete and designed to carry its own weight and any imposed a loading, spanning between supporting members in a structure. Supports for floors are typically beams, columns or walls. This report was conducted for the constructing the swimming pools floor slab which is place at 3rd floor of carpark buildings. The objective of this report is to explain the method of concreting the swimming pools slab. It will focus on the process of concreting the slab including tests done before pouring concrete into the form work. This report also will explain the type of waterproofing that is used in this construction.